Evaluation of visual and instrument shade matching - Okubo, Scott R.; Kanawati, Ali; Richards, Mark W.; Childressd, Steve (The Journal of prosthetic dentistry, 1998)
Statement of problem. Visual color matching to determine shades in dentistry is inconsistent and unreliable. If accurate, instrumental measurement of tooth color would provide objective, quantified data to match natural teeth to clinical shade guides. Purpose. This study evaluated and compared the ability of a new computerized colorimeter and a simple visual test to match ceramic shade guide teeth. Material and methods. Thirty-one (n = 31) observers with normal color vision were allowed unlimited time to match one set of Vita Lumin shade guide teeth to the corresponding shade guide teeth of a second Vita Lumin shade guide. The same test was administered to 14 of the observers several months later to determine within-subject variability. A computerized colorimeter (Colortron II) equipped with a positioning guide was used to measure the middle third of each shade guide tooth. Through a “match tool” present in the computer’s software, readings from one shade guide were matched with readings of the other shade guide by using CIELAB measurements and ΔE values. The mean number of correct matches by the colorimeter and of correct matches in visual test were compared with a 1-tailed t test. Repeatability for both tests was determined with a paired t test. Results. The Colortron II instrument correctly matched 8 of the 16 tabs (50% correct), whereas visual matching by examiners averaged 7.7 of 16 correct matches (48% correct) (standard deviation 2.7). No statistically significant differences existed between the 2 methods. The colorimeter demonstrated 100% repeatability and the visual test demonstrated fair repeatability (correlation coefficient r = .60). Conclusions. Shade determination by visual means was inconsistent. Accuracy of a new colorimeter in matching porcelain shade guide teeth was only slightly better. (J Prosthet Dent 1998;80:642-8.)